Sarapan dan jajan berhubungan dengan kemampuan konsentrasi pada remaja - Mohammad Muchtar; Madarina Julia; Indria Laksmi Gamayanti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2011)
Background: Adolescence is a phase that a human has to pass through in life to become an adult. Bureau of Statistical Centre (1999) reported that total number of adolescent people from 10-19 years old group in Indonesia is about 22% of its total population. High school adolescent often does not have breakfast due to many different reasons such as being in a hurry when going to the school. Breakfast is able to provide carbohydrate for increasing blood glucose supply. In a normal blood glucose supply, passion and concentration as a student would be better so that it makes positive impact to raise productivity.Objective: This study aimed to define correlation between breakfast and have snack at break time habit with concentration capability on high school adolescent in Palangka Raya city.Method: This study was an observational research in cross sectional design. The number of research subject for prevalence test were 106 students for not breakfast group which in screening result were not in anemic condition, while for hypothesis test the mean difference for the two independent groups the total number of subject were 80 persons that consist of 40 subjects for breakfast group and 40 subjects for not breakfast group. Data collection was obtained from body weight and height measurement to explore nutritional status; food recall method to give information of breakfast and have snack at break time, energy, carbohydrate, protein and fat intake; digit symbol and digit span test to explore concentration capability to visual and audio information. The data was processed and analyzed in analytic descriptive way using Spearman correlation test and t-test.Results: This study indicated that 37.7% - 38.8% adolescent in SMAN 1 Pahandut Palangka Raya did not have breakfast. Analytical statistic result showing adolescent who has breakfast has significantly higher concentration capability (using digit symbol and digit span test) than adolescent group who did not have breakfast (p<0.05). Having snack at break time adolescent group had significantly higher concentration capability by using digit symbol test than adolescent group who did not have snack at break time (p<0.05).Conclusion: There was correlation between breakfast and have snack at break time with concentration capability on high school adolescent.